Biomimetic nanomaterial-facilitated oxygen generation strategies for enhancing tumour treatment outcomes - Yang, Zhongwen; Shi, Changsong; Cheng, Dongliang; Wang, Yu; Xing, Yan; Du, Fanfan; Wu, Fangfang; Jin, Yao; Dong, Yueli; Li, Mengli (Frontiers in Bioengineering and Biotechnology, 2022)
Hypoxia, as a typical hallmark of the tumour microenvironment (TME), has been verified to exist in most malignancies and greatly hinders the outcome of tumour treatments, including chemotherapy, photodynamic therapy, radiotherapy, and immunotherapy. Various approaches to alleviate tumour hypoxia have been reported. Among them, biomimetic nanomaterial-facilitated tumour oxygenation strategies, based on the engagement of human endogenous proteins, red blood cells, the cell membrane, and catalase, are the most impressive due to their excellent tumour active-targeting ability and superior tumour-selective capability, which, however, have not yet been systematically reviewed. Herein, we are ready to describe the current progress in biomimetic nanomaterial-facilitated tumour oxygenation strategies and corresponding improvements in tumour treatment outputs. In this review, the underlying mechanism behind the superior effect of these biomimetic nanomaterials, compared with other materials, on alleviating the hypoxic TME is highlighted. Additionally, the ongoing problems and potential solutions are also discussed.